Foreign Ownership, Firm Performance, and the Geography of Civic Capital - Matthias Burker; Chiara Franco; Gaetano Alfredo Minerva (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
It is well established in the literature that foreign affiliates are subject to a series of governance and assimilation costs that deteriorate their performance. This is particularly relevant for firms which have been recently acquired by foreign investors. We employ the variation in civic capital across Italian provinces as an exogenous determinant of these governance costs. We derive the testable implication that there should be a clean evidence of a negative effect of foreign ownership on performance in areas where civic capital is low. As the level of local civic capital increases, this reduces the scope for internal transaction costs, and makes the governance of foreign affiliates easier, and their performance better. We take this prediction to the data and find confirmation of our conceptual framework. Our analysis underlines the importance of the geographic heterogeneity of informal institutions when analyzing the effect of foreign ownership on firm performance.
Keywords: F21; F23; D21; D23; R30; Z13; 330